The Role of Sense of Belonging in Self-Stigma among People with Serious Mental Illnesses - Treichler, Emily B. H. (Psychiatr Rehabil J, 2017)
OBJECTIVE: Self-stigma significantly impacts people with serious mental illnesses. Evidence from other marginalized groups indicates that sense of belonging may buffer these impacts. The purpose of this study was to assess buffering of self-stigma by sense of belonging among this population, including the relationship between these effects and self-identification in other marginalized groups. METHODS: 267 adults with serious mental illnesses completed demographic, self-stigma, exposure to stigma, and sense of belonging measures. Regression analyses were conducted to determine whether sense of belonging buffered self-stigma, and, if so, whether those effects vary by race and gender identification. RESULTS: Sense of belonging buffered self-stigma. Self-identification with other marginalized groups did not impact the buffering effect. CONCLUSIONS AND IMPLICATIONS FOR PRACTICE: Sense of belonging can protect against self-stigma. Self-stigma interventions should integrate components that improve sense of belonging, including community integration. These components should be flexible to meet the cultural context of individual consumers. Key words: Self-stigma, serious mental illness, sense of belonging, race, gender